Selection of Rice (Oryza sativa L.) T1 for Sweet14 Gene Resistance to Bacterial Leaf Blight Disease - M. Dzaky Syadenta; Sri Utami; Fatin Fathirah; Noor Shahira, M.Y; Zulkifli Ahmad Seman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is a major rice disease responsible for significant yield losses in Asia. One effective strategy to control this disease is the development of genetically resistant rice varieties. The xa5 mutant allele, an altered form of the TFIIAγ5 gene, is known to confer broad resistance to BLB. This study aimed to screen T1 generations of rice edited at the TFIIAγ5 gene and assess their resistance to BLB. PCR analysis of the T1 generation revealed the presence of Cas9 gene sequences in some edited lines, indicating inheritance of the transgene from the T0 generation. DNA sequencing of the target site confirmed the presence of small mutations that may alter the function of the TFIIAγ5 gene, rendering it resistant. Disease inoculation assays showed that some T1 lines had significantly shorter lesions than wild-type controls, with lesion length reductions of up to 70%. These results indicate that TFIIAγ5 editing successfully mimics the function of the xa5 allele, conferring resistance to BLB. In conclusion, editing the TFIIAγ5 gene using the CRISPR/Cas9 system is an effective approach to producing BLB-resistant rice and contributes to the development of new, more sustainable, and environmentally friendly varieties.